Elimination of salicide residues in wafer fabrication front-end pre-metal layer cleaning process - Ong, Johann (2022)
Wafer fabrication for integrated circuit is one of the most complicated process in semiconductor manufacturing industry. High yield is always the ultimate goal to achieve hence a good defect management is the key to ensure the goal is met. Salicide residue is a major defect in SilTerra wet etching process. The defect is contributing a total of 1% loss in overall wafer fab sort yield, that is an equivalent to USD$ 5 million loss per year. The objectives for this research is to identify the root cause and determine the element of the residue defect in the wafer substrate at Salicide Pre-Clean wafer fabrication process. Once this has been achieved, next is to determine a novelty solution to reduce the residue defects and finally validate the effectiveness of the novel solution in reducing the salicide residue defects. An investigation of one factor at the time has been conducted with various experiments including screening all the hardware resources available at SilTerra fab by using ANOVA studies. The result has concluded that the salicide residue consists of carbon defect is observed after Salicide Pre-Clean step when the standard diluted hydrofluoric acid (dHF) is used by the wet station equipment to clean the product wafers. This project has discovered an innovated solution to minimize the chemical contact on the wafer has resulted in reducing the post clean defects residue by 80% and eliminate 1% of the total product sort yield loss which is equivalent to approximately USD$ 5 million per year. The procedure had been qualified and implemented successfully in SilTerra and therefore eliminating the yield loss issue.